High-entropy alloys as magnetic shielding materials in low-frequency wireless power transmission - Cheng-Hsien Yeh; Chia-Hua Hu; Hsuan-Ta Wu; Wen-Dung Hsu; Bernard Haochih Liu; Peter K. Liaw; Chuan-Feng Shih (Materials Today Advances)
Soft magnetic materials are required to exhibit high saturation magnetization and low coercivity. Iron-based metal alloys, such as FeMnZn, are commonly used commercial soft magnetic materials with electromagnetic shielding functions. However, these alloys generally exhibit low saturation magnetization, poor high-temperature stability, and significant magnetic losses. In recent years, many research groups have highlighted the excellent soft magnetic properties of high-entropy alloys (HEAs). This study develops new HEA powders with superior soft magnetic characteristics for applications in low-frequency magnetic shielding components. The research found that the FeCoNiSiCuNb HEA, under appropriate ball-milling and annealing conditions, exhibits high saturation magnetization and excellent high-temperature properties, retaining over 50 % of its magnetism even at 700K. At an operating frequency of 100 kHz, compared to FeMnZn, the real permeability of the FeCoNiSiCuNb HEA is increased by 2.25 times. Preparing this HEA material as a magnetic shielding material can lead to higher inductance, a coupling coefficient increased to 0.84, and a transmission efficiency improvement of 19 %, demonstrating the potential of high-entropy alloys in wireless charging applications.